Somatotropina bovina recombinante (rbST) e grupos raciais sobre a precocidade reprodutiva de cabras - Rodrigues, Luciana [UNESP]; Gonçalves, Heraldo César [UNESP]; Cañizares, Gil Ignácio Lara [UNESP]; Menezes, Jakilane Jacque Leal [UNESP]; Ribeiro, Marcela Silva [UNESP]; Medeiros, Brenda Batista Lemos [UNESP] (My University, 2010)
The objective of this work was to evaluate the effect of rbST and breed group on the reproductive precocity of goat females. Eighteen goat females of Alpine breed and breed groups 1/2 Boer + 1/2 Alpine (1/2 BA) and 3/4 Boer + 1/4 Alpine (3/4 BA) were used, distributed in two homogeneous groups of 9 animals, received treatments: Group 1-0,3 mg of recombinant bovine somatotropin by kg of body weight each 14 days and Group 2 - control and aplication was subcutaneous. Animals from control group received saline solution in same dose and interval. The administration of hormone begins after weaning of animals (approximate 45 days of age). The train of the development of females was made by weighed weekly until reaching the previously definitive weight of 30 kg of live weight (LW). For evaluation of the reproductive performance it was made observations of the signals related to the oestrus. The characteristics evaluated was: Weight gain at born until weaning, weaning at 120 days, 150 and 180 days of age, weight to the oestrus, age to the rutting and the 30 age to kg of LW. It was not observed influence of growth hormone and the breed group for weight to rutting, age to rutting and age to reach 30 kg LW. The use of rbST in growth females did not modify the parameters of sexual precocity.
Recombinant bovine somatotropin (rbST) and breed group in reproductive precocity of goat females
Keywords: Goats; Growth hormone; Live weight; Oestrus; Puberty; Animalia; Bovinae; Capra hircus